Faktor yang Berhubungan dengan Kejadian Penyakit TBC pada Anak di Puskesmas Topoyo Provinsi Sulawesi Barat - Kasmiati Kasmiati; Marniati Marniati; Latifa Nur; Pahria Pahria; Lina Fitriani (STIKes Ibnu Sina Ajibarang, 2024)
Child TB is on of the causes of illness and weakness that often occurs in children WHO data 2018 states that there are 1.1 million cases of TB in children which are affected by nutritional status, immunization, contact history, and environment. Factors that influence the incidence of tuberculosis in children using a case control approach The population in this study were all pediatric patients who visited the topoyo health center. Data collection was carried out using a questionnaire and observation sheets were then processed and analyzed using a statistical program. The result: the study showed that there was a relationship, immunization, contact history, of TB disease in children in the working area of the topoyo health center. Conclusion: the incidence of TB in children is closely related to immunization factors, and the environment to TB in children.